AKTIVITAS ANTIINFLAMASI EKSTRAK ETER KULIT BATANG TENGGULUN (Protium javanicum Burm) TERHADAP EDEMA PADA TIKUS WISTAR YANG DIINDUKSI DENGAN KARAGENAN - Tia Santika Dewi, A. A.; Puspawati, Ni Made; Suarya, Putu (Jurnal Kimia (Journal of Chemistry); Vol. 9, no. 1 Januari 2015DO - 10.24843/JCHEM.2015.v09.i01.p03, 2015)
Stem bark of Tenggulun ( Protium javanicum , Burm) has been used traditionally by Balinese people as anti-inflammatory agents. This research aimed to analyze phytochemical contents and to evaluate anti-inflammatory activity of stem bark ether extract of Tenggulun. Phytochemical study was done qualitatively using phytochemical reagents. Anti-inflammatory activity was evaluated on edema rats induced by carrageenan with given extract at doses of 125, 250, and 500 mg/kg b.w. Diclophenac sodium was used as the positive control. Phytochemical study revealed that the stem bark ether extracts consisted of alkaloids, steroids, terpenoids, and phenolic compounds.  Anti-inflammatory activity test  results showed at a dose of 125 mg/kg b.w, the extract only inhibit inflammation by 34.54%, while a dose of 250 mg/kg b.w gave inhibition of inflammation by 94.34%, and a dose of 500 mg/kg b.w can inhibit inflammation by 96.11% during 360 minutes observation. Probit analysis gave ED 50 value of 103.252 mg/kg B.W.
Keywords: Anti-inflammatory activity, stem bark of Tenggulun